Transcriptional and Epigenetic Regulation by the Mechanistic Target of Rapamycin Complex 1 Pathway - Laribee, R. Nicholas (J Mol Biol, 2018)
Nutrient availability impacts health such that nutrient excess states can dysregulate epigenetic and transcriptional pathways to cause many diseases. Increasing evidence implicates aberrant regulation of nutrient signaling cascades as one means of communicating nutrient information to the epigenetic and transcriptional regulatory machinery. One such signaling cascade, the mechanistic target of rapamycin complex 1 (mTORC1), is conserved from yeast to man, and it is deregulated in diverse disease states. The catalytic subunit of the mTORC1 kinase complex (Tor1 or Tor2 in budding yeast and mTor in mammals) phosphorylates several downstream effectors regulating transcriptional and translational responses controlling growth and proliferation. Delineating mechanisms of cytoplasmic nutrient mTORC1 activation continues to be a major research focus. However, Tor kinases localize not only to the cytoplasm, but they also are found in the nucleus where they selectively bind and regulate genes controlling cellular metabolism and anabolism. The nuclear mTORC1 functions are now beginning to be defined, and they suggest that mTORC1 has a critical role in regulating the complex transcriptional activities required for ribosomal biogenesis. The mTORC1 pathway also interacts with epigenetic regulators required for modifying chromatin structure and function to control gene expression. Because altered nutrient states exert both individual and transgenerational phenotypic changes, mTORC1 signaling to chromatin effectors may have a significant role in mediating the effects of diet and nutrients on the epigenome. This article will discuss the recent inroads into the function of nuclear mTORC1 and its role in epigenetic and transcriptional regulation.